The effect of pituitrin on postoperative outcomes in patients with pulmonary hypertension undergoing cardiac surgery: a study protocol for a randomized controlled trial - Kong, Lingchen; Lv, Meng; Qiao, Chang-long; Sun, Xia-xuan; Du, Wen-ya; Li, Quan (Frontiers in Cardiovascular Medicine, 2024)
Background The vasoplegic syndrome is one of the major consequences of cardiac surgery. If pulmonary hypertension is additionally involved with vasoplegic syndrome, circulation management becomes much more complicated. According to previous studies, pituitrin (a substitute for vasopressin, which contains vasopressin and oxytocin) not only constricts systemic circulation vessels and increases systemic circulation pressure but also likely decreases pulmonary artery pressure and pulmonary vascular resistance. The aim of this study is to investigate whether pituitrin is beneficial for the postoperative outcomes in patients with pulmonary hypertension undergoing cardiac surgery. Methods and analysis The randomized controlled trial will include an intervention group continuously infused with 0.04 U/(kg h) of pituitrin and a control group. Adult patients with pulmonary hypertension undergoing elective cardiac surgery will be included in this study. Patients who meet the conditions and give their consent will be randomly assigned to the intervention group or the control group. The primary outcome is the composite endpoint of all-cause mortality within 30 days after surgery or common complications after cardiac surgery. Secondary outcomes include the incidence of other postoperative complications, length of hospital stay, and so on. Discussion Pituitrin constricts systemic circulation vessels, increases systemic circulation pressure, and may reduce pulmonary artery pressure and pulmonary vascular resistance, which makes it a potentially promising vasopressor during the perioperative period in patients with pulmonary hypertension. Therefore, evidence from randomized controlled trials is necessary to elucidate whether pituitrin influences outcomes in patients with pulmonary hypertension following cardiac surgery.